Improving Mathematical Creative Problem Solving Skill of Male and Female Students through Situation-Based Learning - Isrok’atun (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2017)
The purpose of this research was to investigate the improvement of male and female students’ mathematical Creative Problem Solving (CPS) ability as a result of Situation-Based Learning. The quasi experimental design was used by involving two methods, namely Situation-Based Learning and conventional method. The population of the research was high school students in Central Java Province. The research instrument used in the study was CPS test. The data were analyzed based on the students’ gender. The research resulted in the following conclusions: (1) the improvement of students’ mathematical CPS ability taught under SBL was higher than those who were taught using conventional method based on students’ gender, and (2) there was no interaction between learning model and gender on the improvement of students’ mathematical CPS ability.